Motivasi Belajar Mempengaruhi terhadap Hasil Belajar Siswa Kelas V di Sekolah Dasar - Harlen Simanjuntak (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
The purpose of this study was to determine how much motivation to learn affects the learning outcomes of fifth grade students in elementary schools 064021 Medan City. The method used is a quantitative correlational method with data collection techniques by means of library research and field research through interviews, observations and documentation. With the results of the calculation of the correlation number of variable X (learning motivation) to the variable Y (learning outcomes) of 0.965. This means that the effect of learning motivation on student learning outcomes in grade V SDN 064021 Medan Helvetia Medan city is very high.